1988
DOI: 10.3758/bf03209384
|View full text |Cite
|
Sign up to set email alerts
|

Concept learning by pigeons: Matching-to-sample with trial-unique video picture stimuli

Abstract: Pigeons were trained to match-to-sample with several new methodologies: a large number of stimuli, computer-drawn color picture stimuli, responses monitored by a computer touch screen, stimuli presented horizontally from the floor, and grain reinforcement delivered onto the picture stimuli. Following acquisition, matching-to-sample concept learning was assessed by transfer to novel stimuli on the first exposure to pairs of novel stimuli. One group (trial-unique), trained with 152 different pictures presented o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
182
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(192 citation statements)
references
References 34 publications
7
182
0
3
Order By: Relevance
“…Although previous studies have shown better than chance oddity transfer in pigeons (e.g., Lombardi, Fachinelli, & Delius, 1984), this article is the first example in the literature demonstrating that pigeons can fully learn an abstract concept of oddity, and one of the few examples of pigeons fully learning any abstract concept. Other examples would be pigeons fully learning the abstract concept of matching-to-sample with video cartoons presented from the chamber floor (Wright, 1997;Wright et al, 1988) and pigeons fully learning an abstract concept of same/different with digitized travel slides (Katz & Wright, in press). The present study showed that the OPE was a major contributing factor to acquisition for the oddity group without sample reward.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have shown better than chance oddity transfer in pigeons (e.g., Lombardi, Fachinelli, & Delius, 1984), this article is the first example in the literature demonstrating that pigeons can fully learn an abstract concept of oddity, and one of the few examples of pigeons fully learning any abstract concept. Other examples would be pigeons fully learning the abstract concept of matching-to-sample with video cartoons presented from the chamber floor (Wright, 1997;Wright et al, 1988) and pigeons fully learning an abstract concept of same/different with digitized travel slides (Katz & Wright, in press). The present study showed that the OPE was a major contributing factor to acquisition for the oddity group without sample reward.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly unlikely that our animals had acquired a symmetry concept, since their level of performance when initially faced with the second or the third pair of patterns was not importantly superior to that at the beginning of the first pair. Additionally numerous studies could show that pigeons need a large number of exemplars until switching to a more abstract cognitive strategy [32] and are not as easily trained to categorize 'symmetry' as suspected previously [14]. However, the unexpected unilaterality of left hemispheric memory with a partial absence of interhemispheric transfer are not altered by the fact that the stimuli could in principle be grouped into a symmetric and an asymmetric group.…”
Section: Methodsmentioning
confidence: 99%
“…These more recent experiments have shown that experience with several examples of same/different relations increases the tendency of pigeons and both old-and new-world monkeys to transfer that training to new stimuli (Katz, Wright, & Bachevalier, 2002;Wright et al, 1988;Wright, Rivera, Katz & Bachevalier, 2003). However, no such constraint or limitation of stimulus set size seems to hold for chimpanzees (Oden, Thompson, & Premack, 1988).…”
Section: Same/different Learningmentioning
confidence: 96%
“…In recent years, studies of both birds and mammals have revealed even better evidence for the transfer of conceptual same/different discriminations (e.g., Blaisdell & Cook, 2005;Katz, Wright, & Bachevalier, 2002;Mercado, Killebrew, Pack, Macha, & Herman, 2000;Oden, Thompson & Premack, 1988;Pepperberg, 1987;Wright, Cook, Rivera, Sands, & Delius, 1988;see Wasserman, Young, &Cook, 2004 and for reviews). These more recent experiments have shown that experience with several examples of same/different relations increases the tendency of pigeons and both old-and new-world monkeys to transfer that training to new stimuli (Katz, Wright, & Bachevalier, 2002;Wright et al, 1988;Wright, Rivera, Katz & Bachevalier, 2003).…”
Section: Same/different Learningmentioning
confidence: 99%